Effects of Greenshell™ mussel intervention on biomarkers of cartilage metabolism, inflammatory markers and joint symptoms in overweight/obese postmenopausal women: A randomized, double-blind, and placebo-controlled trial - Abshirini, Maryam; Coad, Jane; Wolber, Frances M.; von Hurst, Pamela; Miller, Matthew R.; Tian, Hong Sabrina; Kruger, Marlena C. (Frontiers in Medicine, 2022)
Objective: To investigate the effect of whole greenshell mussel (GSM) powder on biomarkers of cartilage metabolism, inflammatory cytokines, and joint symptoms in postmenopausal women with overweight/obesity and joint discomfort. Design: Fifty-five postmenopausal women with overweight/obesity were randomly assigned to receive 3 g/day whole GSM powder or placebo for 12 weeks. Cartilage turnover biomarkers urinary C-telopeptide of type II collagen (CTX-II) and serum cartilage oligomeric matrix protein (COMP) were measured at baseline, week 6 and 12. Plasma cytokines were measured at baseline and week 12. Joint pain and knee-related problems were assessed at baseline and week 12 using a 100 mm Visual Analogue Scale (VAS) and the Knee injury and Osteoarthritis Outcome Score (KOOS) questionnaire, respectively. Results: Forty-nine participants completed the study (GSM n=25, placebo n=24). After 12 weeks, urinary CTX-II showed no significant change over time or between the groups (interaction effect P=0.1). However, in women with symptomatic knees, a significant difference was noted between the group (treatment effect P=0.04), as it was lower in the GSM group compared to placebo group at week 6 (P=0.04) and week 12 (P=0.03). Serum COMP and plasma cytokines were not affected. GSM supplementation showed greater reduction in the VAS pain score than placebo (-13.2±20.3 vs -2.9±15.9; P=0.04). No significant change in KOOS domains between the two groups was observed. Conclusions: Oral supplementation of whole GSM powder at 3 g/day may slow down the degradation of type II collagen in postmenopausal women with symptomatic knees. GSM treatment conferred clinical benefit on overall joint pain. No significant effect was noted for cytokines, suggesting that GSM may act within the joint microenvironment rather than at the systemic level.